Copy Number Variation of Immune-Related Genes and Their Association with Iodine in Adults with Autoimmune Thyroid Diseases - Xing Jin; Yunfeng Guan; Hongmei Shen; Yi Pang; Lixiang Liu; Qingzhen Jia; Fangang Meng; Xiaoye Zhang (International Journal of Endocrinology)
Background. Autoimmune thyroid diseases (AITD) are complex conditions that are caused by an interaction between genetic susceptibility and environmental triggers. Iodine is already known to be an environmental trigger for AITD, but genes associated with susceptibility need to be further assessed. Therefore, the aims of this study were to assess the association between copy number variations (CNVs) and AITD, to identify genes related with susceptibility to AITD, and to investigate the interaction between iodine status and CNVs in the occurrence of AITD. Methods. Blood samples from 15 patients with AITD and 15 controls were assessed by chromosome microarray to identify candidate genes. The copy number of candidate genes and urinary iodine level was determined in adults from areas of different iodine statuses including 158 patients and 181 controls. Results. The immune-related genes, SIRPB1 and TMEM91, were selected as candidate genes. The distribution of SIRPB1 CNV in AITD patients and controls was significantly different and was considered a risk factor for AITD. There was no significant association between urinary iodine level and candidate gene CNVs. Conclusion. SIRPB1 CNV and an excess of iodine were risk factors for AITD, but an association with the occurrence of AITD was not found.